2020
DOI: 10.2174/1874944502013010094
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Poor Quality of Sleep among Prisoners in Mettu Town Prison, Oromia, South West Ethiopia, 2019

Abstract: Background: Sleep is one of the basic needs of human beings and is important to their health; sleeping problem has a wide range of causes, including medical and psychological. However, evidence on the burden of sleep problems in low-income countries is lacking. When compared to the general population, the risks of having poor sleep quality are substantially higher in prisoners. However, the prevalence of poor sleep quality among prisoners at national level is not known. Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 10 publications
0
15
1
Order By: Relevance
“…did not describe the threshold used for PSQI nor did they report the prevalence of poor sleep measured by the PSQI global score. This, again, means thatAbdu and Hajure (2020) andAcar et al (2019) overestimated the prevalence of poor sleep quality by including a score of 5 as poor-rather than good-quality sleep(Backhaus et al, 2002) Ishfaq and Kamal (2019). measured sleep problems (amongst other psychiatric symptomology) with the 23-item DSM-5 cross-cutting symptoms measure (CCSM), and the prevalence of sleep problem was estimated from one question and should be evaluated with caution due to this crude measurement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…did not describe the threshold used for PSQI nor did they report the prevalence of poor sleep measured by the PSQI global score. This, again, means thatAbdu and Hajure (2020) andAcar et al (2019) overestimated the prevalence of poor sleep quality by including a score of 5 as poor-rather than good-quality sleep(Backhaus et al, 2002) Ishfaq and Kamal (2019). measured sleep problems (amongst other psychiatric symptomology) with the 23-item DSM-5 cross-cutting symptoms measure (CCSM), and the prevalence of sleep problem was estimated from one question and should be evaluated with caution due to this crude measurement.…”
mentioning
confidence: 99%
“…According to the measure, ISI ≥ 15 would distinguish "clinical insomnia", whereas ≥10 and ≥9 are part way in the "subthreshold" range of scores of 8-14(Morin et al, 2011).There was further inconsistency in the use of PSQI score thresholds withDewa et al (2017a), Getachew et al (2020, and Harner and Budescu (2014) using the suggested PSQI > 5 for distinguishing poor sleep. However,Abdu and Hajure (2020) andAcar et al (2019) used PSQI ≥ 5 Barker et al (2016). did not describe the threshold used for PSQI nor did they report the prevalence of poor sleep measured by the PSQI global score.…”
mentioning
confidence: 99%
“…Chronic illness: Illnesses such as asthma, diabetes mellitus, stroke, kidney stone, hypertension that can be managed, but cannot be cured and have a greater risk of developing a poor quality of sleep. 56 …”
Section: Methodsmentioning
confidence: 99%
“…44 Chronic illness: Illnesses such as asthma, diabetes mellitus, stroke, kidney stone, hypertension that can be managed, but cannot be cured and have a greater risk of developing a poor quality of sleep. 56 Risk perception of COVID-19 infection: Was assessed by two psychological dimensions; perceived susceptibility and perceived severity. The first dimension was proxied by how likely one considered oneself (his/her family) would be infected with COVID-19 if no preventive measures will be taken.…”
Section: Variable Measurement and Definition Of Termsmentioning
confidence: 99%
“…Amongst these eight studies, five presented on prevalence. These included: Geng et al (2020), which found high prevalence rates for insomnia (26.2%) and poor sleep quality (45.9%) in a Chinese prison; Abdu and Hajure (2020) found 77.1% and Getachew et al (2020) found 53.9% of prisoners had poor sleep quality in Ethiopian prisons; Chinichian and Alemohammad (2020) found 87.7% prevalence of poor sleep quality in a prison in Iran; and Dewa et al (2017b) reported prevalence of insomnia disorder of 61.6% in England.…”
Section: Secondary Analysismentioning
confidence: 99%